The Karabagh conflict in the context of the United States’ global policy - Farahile Babaeva Shukurova (Американська історія і політика, 2017)
The aim of the Minsk group of OSCE established on March 1992 was to mediate the peaceful solution of the Armenia-Azerbaijan Nagorno-Karabakh conflict: “From December 1996, the Minsk Group is co-chaired by three states – Russia, the United States and France. But unfortunately the conflict still remains unresolved. Zero progress has been reached so far in the negotiation mediated by the Minsk group. Armenia is not interested in resolution of the conflict. It tends to keep the position of neither fire, nor peace. But in the early April of 2016, as result of subversion of Armenian armed forces the tension in the contact line of troops which was followed by numerous human causalities, once more confirmed that remaining the conflict frozen might would always cause the intense war.” But the international mediators for some reason wouldn’t demonstrate any unequivocal position upon this case although they support the territorial integrity of Azerbaijan. It is expected that the members of the Minsk group of the OSCE, as well as global community would take precise measures to solve this problem fairly. Failure to adhere to the principle of justice would draw to crisis not only the region, but also worldwide. The reality is that, the USA, Russia and France wouldn’t bring the aggressor down as a neither permanent member of the UN SC, nor as a member states. It is a painful and thought-provoking truth, but it is still the case.